2011
DOI: 10.1007/jhep02(2011)046
|View full text |Cite
|
Sign up to set email alerts
|

Two and three-point correlators of operators dual to folded string solutions at strong coupling

Abstract: A particular analytic continuation of classical string solutions having a single AdS 5 spin is considered. These solutions describe strings tunnelling from the boundary to the boundary of AdS 5 . We use the Legendre transform of the dimensionally regularised action of these solutions to evaluate the 2-point functions of the dual operators, holographically. Subsequently, we evaluate the structure coefficient of correlators involving two operators with spin S and a BPS state, at strong coupling. Our expressions … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 50 publications
(91 reference statements)
0
27
0
Order By: Relevance
“…We fix h 0 , in analogy with the unflavored KS solution [12], by requiring that h(τ ) goes to zero at some finite UV cut off (before reaching the Landau pole where the supergravity approximation is no longer valid) for any number of flavors. 8 In this case h 0 (N f ), as can be seen from the left plot of figure 1, is a monotonically decreasing function and as a consequence the glueball mass increases with the number of flavors.…”
Section: Jhep07(2015)003 4 Entanglement Entropy and Massless Flavorsmentioning
confidence: 72%
See 1 more Smart Citation
“…We fix h 0 , in analogy with the unflavored KS solution [12], by requiring that h(τ ) goes to zero at some finite UV cut off (before reaching the Landau pole where the supergravity approximation is no longer valid) for any number of flavors. 8 In this case h 0 (N f ), as can be seen from the left plot of figure 1, is a monotonically decreasing function and as a consequence the glueball mass increases with the number of flavors.…”
Section: Jhep07(2015)003 4 Entanglement Entropy and Massless Flavorsmentioning
confidence: 72%
“…7 In [14] the authors examined the effect of two alternative possibilities on the Wilson loops calculation. 8 See more about the effect of such a choice for the UV cutoff on the IR physical quantities in [31]. EE is even more less affected, since in (2.9) we are subtracting the contribution from the UV.…”
Section: Jhep07(2015)003 4 Entanglement Entropy and Massless Flavorsmentioning
confidence: 99%
“…This AdS/CFT correspondence provides a new fascinating way to understand the strong coupling region of SYM theory by investigating the dual classical gravity or string theory. Many authors calculated the three-point correlation function of various heavy operators and showed that the string theory calculations for the coupling between two heavy operators and one marginal operator exactly coincide with the results of the gauge theory [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. In this paper, our goal is to investigate the correlation functions of more nontrivial solitonic strings moving in AdS 5 Â S 3 and to compare those results with ones of the gauge theory.…”
Section: Introductionmentioning
confidence: 94%
“…For example, in the case of N = 8 supergravity the double-soft limit reveals the E 7(7) symmetry algebra of the scalar 1 Another important class of observables is that of correlation functions of gauge invariant operators. For some recent progress on this front see [15][16][17][18][19][20] and references therein. 2 For detailed reviews on this and other related subjects see [21][22][23].…”
Section: Introductionmentioning
confidence: 99%